Alternative poverty measures in Chile, 1990-2015 - Martner, Gonzalo D. (2018)
Poverty levels in Chile have decreased since 1990, in a context of sustained GDP and family income growth. The intensity of this evolution is controversial based on the different measure methods applied. Absolute, relative, and multidimensional poverty indexes are compared. It is concluded that, based on the same income survey, resulting measures highly depend on poverty definitions. Evidence is presented for the 1990-2015 period.